2022
DOI: 10.3390/ma15144911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium Salt (MgCl2 and MgSO4) on the Microstructures and Properties of Ground Granulated Blast Furnace Slag (GGBFS)-Based Geopolymer

Abstract: The use of seawater to prepare geopolymers has attracted significant research attention; however, the ions in seawater considerably influence the properties of the resulting geopolymers. This study investigated the effects of magnesium salts and alkaline solutions on the microstructure and properties of ground-granulated-blast-furnace-slag-based geopolymers. The magnesium salt–free Na2SiO4-activatied geopolymer exhibited a much higher 28 d compressive strength (63.5 MPa) than the salt-free NaOH-activatied geop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 72 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…The use of alkali-activated binders is a promising approach, since they can be derived by activating industrial wastes of different origins. Among many possible sources, ground granulated blast-furnace slag (GGBFS) [1], discarded glasses unfit to be used in the production of new glass items [2], fly ash [3,4], and red mud [5] have been used to formulate alkali-activated binders. However, these materials suffer from extreme brittleness and low dimensional stability, as reported in the literature [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The use of alkali-activated binders is a promising approach, since they can be derived by activating industrial wastes of different origins. Among many possible sources, ground granulated blast-furnace slag (GGBFS) [1], discarded glasses unfit to be used in the production of new glass items [2], fly ash [3,4], and red mud [5] have been used to formulate alkali-activated binders. However, these materials suffer from extreme brittleness and low dimensional stability, as reported in the literature [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Ground-granulated blast furnace slag (GGBFS) is a solid waste largely produced in the iron industry. Zhang et al [4] mixed it with alkaline solutions (NaOH or Na 2 SiO 4 solution) and magnesium salts (MgCl 2 •6H 2 O and MgSO 4 ) to prepare the GGBFS-based geopolymers. It is reported that the magnesium salt-free Na 2 SiO 4 -activatied geopolymer exhibited a much higher 28 d compressive strength (63.5 MPa) than the salt-free NaOH-activated geopolymer (31.4 MPa), with the former mainly containing an amorphous phase (C-(A)-S-H gel) and the latter containing numerous crystals.…”
mentioning
confidence: 99%